(3TQM GdcGajIs - (3eMeO Hf GdMSf GdQVj GdCSJQGHGPj , fLe GdOjf,J (B686 (3g` s ((3UdGM Hf Ydj GdLRjGfj GdCgfhej s)
(3ChdgG (B:s
(3hHYO, abO WdH Edj ef GYJfi HUdGM MGdg, hCSYag HeG JSYg ebOQJj ef ebJQMGJ BeGdg s
(3BNQgG (B:s
(3hdG jdj gPg GdRjGOI gGA GdScJ HNdGa RjGOI GdEfcGQ, dCf gPg GdgGA JROGO EPG de JbUO Gdhba Je GdcJGH s
(3fSNI KGfjI JJab aj ChdgG eY GdLRA GdChd ef GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3ajg VHWs
(3cJHgG GdfGSN dYfGjI GdMSjf Hf jMji Hf eMeO Hf MfTs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddehVhYGJ s
(3bQf GdfSN (B:s
Keywords: (3GdfMhs